Suicidal Ideation in Newly-Diagnosed Chinese Cancer Patients - Zhang, Yongfu; Li, Wengao; Zhang, Zijun; Sun, Hengwen; Garg, Samradhvi; Yang, Yuan; Wang, Hongmei (Frontiers in Psychiatry, 2020)
Objective: Suicide is one of the main reasons cited behind the death rate of cancer, and suicidal ideation (SI) is the first step towards it. This study aimed to investigate the prevalence and associates of suicidal ideation in newly-diagnosed Chinese cancer patients. Methods: This multicenter study was conducted from January 2018 to September 2019. Eligible participants were asked to complete a Case Record Form (CRF), the Patient Health Questionnaire (PHQ-9), General Anxiety Disorder Questionnaire (GAD-7), Fear of Cancer Recurrence Questionnaire (FCRQ-7), and McGill Pain Questionnaire-Visual Analogue Scale (MPQ-VAS). Univariate analyses and multivariate logistic regression analyses were conducted for assessment. Results: Out of 603 patients, 91 (15.1%, 95%CI: 12.23%-17.96%) reported suicidal ideation in the last two weeks. Physical comorbidities (OR=1.808, P=0.039), childhood adversity experience (OR=5.999, P=0.001), cancer pain (OR=1.828, P=0.047), depression (OR=2.811, P=0.013) and anxiety (OR=6.532, P<0.001) were significantly associated with suicidal ideation. It was also found that patients who regularly exercised were less likely to report suicidal thoughts (OR=0.172, P=0.007). Conclusion: Physical comorbidities, body ache, and mood disturbances are possible risk factors for suicidal ideation that warrant further attention in clinical practice. Preventive measures, such as systematic screening and arrangement for regular check-ups, could be beneficial to lower the risk of suicide.